High-Fat-Diet-Induced Obesity Produces Spontaneous Ventricular Arrhythmias and Increases the Activity of Ryanodine Receptors in Mice - Sánchez, Gina; Araneda, Felipe; Peña, Juan Pedro; Finkelstein, José Pablo; Riquelme, Jaime A.; Montecinos, Luis; Barrientos, Genaro; Llanos, Paola; Pedrozo, Zully; Said, Matilde; Bull, Ricardo; Donoso, Paulina (My University, 2018)
Ventricular arrhythmias are a common cause of sudden cardiac death, and their occurrence is higher in obese subjects. Abnormal gating of ryanodine receptors (RyR2), the calcium release channels of the sarcoplasmic reticulum, can produce ventricular arrhythmias. Since obesity promotes oxidative stress and RyR2 are redox-sensitive channels, we investigated whether the RyR2 activity was altered in obese mice. Mice fed a high fat diet (HFD) became obese after eight weeks and exhibited a significant increase in the occurrence of ventricular arrhythmias. Single RyR2 channels isolated from the hearts of obese mice were more active in planar bilayers than those isolated from the hearts of the control mice. At the molecular level, RyR2 channels from HFD-fed mice had substantially fewer free thiol residues, suggesting that redox modifications were responsible for the higher activity. Apocynin, provided in the drinking water, completely prevented the appearance of ventricular arrhythmias in HFD-fed mice, and normalized the activity and content of the free thiol residues of the protein. HFD increased the expression of NOX4, an isoform of NADPH oxidase, in the heart. Our results suggest that HFD increases the activity of RyR2 channels via a redox-dependent mechanism, favoring the appearance of ventricular arrhythmias.
Keywords: Calcium release channels; Reactive oxygen species (ROS); Redox modifications; Ventricular tachycardia; NADPH oxidase